ANALYSIS OF THE TYPE OF APPROXIMATION OF THE MAGNETIZATION CURVE FOR ELECTROMAGNETIC CONVERTERS OF HIGH CURRENTS - Juraeva Kamila Komilovna; Rustemova Aynura Rustemovna (Research Parks Publishing LLC, 2020)
In the article discuss analyzes the type of approximation of the magnetization curve of a direct current, alternating current, direct current and alternating current magnetic circuit in order to calculate the magnetic circuits of high-current electromagnetic transducers.